Polyethylene Household Waste Recycling and Enhancing by Using Pyrolyzed Black Carbon - Hananni, Adel; Bshara, Moneer; khadoor, Tariq (My University, 2015)
The object of this study is to determine the impact of plastic recycling on the mechanical properties of material in order to begin to change the current precipitin that recycled plastic are low-quality materials or to enhance of its properties by using black carbon which is locally. For this purpose, sample of virgin polymer and recycled plastic wastes filled in black carbon with deferent percentage of carbon were prepared with a locally fabricated singlescrew extruder. Low density polyethylene (LDPE) and High Density Polyethylene (HDPE} were the type of polymer selected as virgin polymer. After the prepared sample tested for tensile test, it was obtained that the properties of recycled material is decreased; For example the modulus of elasticity, tensile stress, ductility for High Density Polyethylene virgin were 891(Mpa) ,25.41(Mpa), 26.6% elongation respectively. Whereas; the modulus elasticity, stress, ductility of High density Polyethylene recycled were 593(Mpa), 20.855 Mpa, 29.5% respectively, after using Pyrolyzed black carbon with 4% by weight the mechanical properties for recycled was 899(Mpa), 28.34 (Mpa), 18.4% elongation respectively. Also; the same percent of carbon was enhanced the properties of recycled Low Density Polyethylene.